’Kicking Sand in the Face of Apartheid’: Segregated Beaches in South Africa - Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2017)
This article makes a contribution to address the overwhelming ’present-mindedness’ of tourism geography scholarship. Using a range of archival sources an analysis is undertaken of the rise and demise of racial segregation on South Africa’s beaches during the period 1953-1989. The division of beach space along racial lines is an aspect of the implementation of what was termed ’petty apartheid’. This analysis reveals that the national government’s attempts to legislate the making of beach segregation were uneven and contested in different coastal centres. By the 1980s, however, mounting opposition and resistance to the apartheid state resulted in the crumbling of beach apartheid and the formal desegregation of beach spaces.